1983
DOI: 10.1111/j.1471-0528.1983.tb06449.x
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective review of cervical cytology in women developing invasive squamous cell carcinoma

Abstract: The records of 93 women who presented with invasive squamous cell carcinoma were searched for evidence of cervical cytology during the years preceding this diagnosis; a search was also made through the files of local laboratories and contact was made with general practitioners and relevant hospital departments. Only 26 (28%) of these 93 women had had a cervical smear at any time before the diagnosis of invasive cancer, and only 11 (12%) had had regular cytological survcillance. Fifteen (60%) had had a smear ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0
2

Year Published

1988
1988
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 14 publications
1
11
0
2
Order By: Relevance
“…There was less variation between the smears from cases and from controls in the percentages of unsatisfactory, which varied between 13-25% among smears from cases and 15-29% among smears from controls. (Mitchell et al, 1988) to 64% (Attwood et al, 1985) previously reported in the predominantly small series of patients with invasive cervical cancer for whom the previous negative smears have been reviewed (Rylander, 1977;Gad & Koch, 1978;Berkowitz et al, 1979;Berkeley et al, 1980;Holman et al, 1981;Morell et al, 1982;Walker et al, 1983: Paterson et al, 1984Gay et al, 1985;Attwood et al, 1985;Graff et al, 1987;Mitchell et al, 1988;Mitchell et al, 1990).…”
mentioning
confidence: 98%
“…There was less variation between the smears from cases and from controls in the percentages of unsatisfactory, which varied between 13-25% among smears from cases and 15-29% among smears from controls. (Mitchell et al, 1988) to 64% (Attwood et al, 1985) previously reported in the predominantly small series of patients with invasive cervical cancer for whom the previous negative smears have been reviewed (Rylander, 1977;Gad & Koch, 1978;Berkowitz et al, 1979;Berkeley et al, 1980;Holman et al, 1981;Morell et al, 1982;Walker et al, 1983: Paterson et al, 1984Gay et al, 1985;Attwood et al, 1985;Graff et al, 1987;Mitchell et al, 1988;Mitchell et al, 1990).…”
mentioning
confidence: 98%
“…Muitos autores (6,18,21,27,28,32,35,36) salientam que podem ocorrer erros no diagnóstico do teste de Papanicolaou.…”
Section: Discussionunclassified
“…Since the early days of screening, there has been considerable interest in exploring the cytological history of women enrolled in the programme who subsequently developed cervical cancer. Several studies during the 1980–90s 1–3 reviewed previously negative smears and proposed misclassification of smears as a potential contributing factor in the development of invasive disease. These findings were also seen in the Leicestershire audit of invasive cervical cancers, 4 which resulted in the issue of errors in cytological interpretation as part of the screening programme, being brought to the media’s attention.…”
Section: Introductionmentioning
confidence: 99%